Inhibition of Malaria Infection in Transgenic Anopheline Mosquitoes Lacking Salivary Gland Cells. - Daisuke S Yamamoto; Megumi Sumitani; Katsumi Kasashima; Hideki Sezutsu; Hiroyuki Matsuoka (PLoS Pathogens, 2016)
Malaria is an important global public health challenge, and is transmitted by anopheline mosquitoes during blood feeding. Mosquito vector control is one of the most effective methods to control malaria, and population replacement with genetically engineered mosquitoes to block its transmission is expected to become a new vector control strategy. The salivary glands are an effective target tissue for the expression of molecules that kill or inactivate malaria parasites. Moreover, salivary gland cells express a large number of molecules that facilitate blood feeding and parasite transmission to hosts. In the present study, we adapted a functional deficiency system in specific tissues by inducing cell death using the mouse Bcl-2-associated X protein (Bax) to the Asian malaria vector mosquito, Anopheles stephensi. We applied this technique to salivary gland cells, and produced a transgenic strain containing extremely low amounts of saliva. Although probing times for feeding on mice were longer in transgenic mosquitoes than in wild-type mosquitoes, transgenic mosquitoes still successfully ingested blood. Transgenic mosquitoes also exhibited a significant reduction in oocyst formation in the midgut in a rodent malaria model. These results indicate that mosquito saliva plays an important role in malaria infection in the midgut of anopheline mosquitoes. The dysfunction in the salivary glands enabled the inhibition of malaria transmission from hosts to mosquito midguts. Therefore, salivary components have potential in the development of new drugs or genetically engineered mosquitoes for malaria control.